Perencanaan Pendirian Usaha Lele Frozen Food - Utomo, Dewangga Tri; Cholid, Idham (Universitas Multi Data Palembang, 2024)
Catfish Frost Aquaponics is a business that combines 2 innovative concepts of aquaponics and frozen food methods. This business offers Lele Frost products containing 4-6 catfish (1kg) that have been given yellow spices. This business is located on Jalan Letjen TNI Dr. H. Ibnu Sutowo No.23 Palembang. The reason for choosing this business is because there are many catfish enthusiasts in Palembang City. Promotion that will be done using social media. Based on the aspect of business feasibility, Lele Frost is declared worthy to run its business and can benefit in the future.